Major Factors Influencing Students' Satisfaction Level Of Online Learning Management System In Multimedia University - Yap, Boon Foo (2005)
This report aims at highlighting major factors influencing quality of online learning management system. It addressess also the students' perception of availability and usage of online learning management system, future improvement and prospects of online learning management system together with users' preference for intercafe design.